Student’s Creative Zig-zag Book: Improving their Concepts Understanding by Using Project Based Learning - Komalasary, Deasy; Rusilowati, Ani; Putra, Ngurah Made Darma (Journal of Primary Education, 2019)
This study aims to describe the application of project-based learning in improving concept understanding through the creativity of making zigzag books. This type of research is a mixed method research with concurrent embedded designs. The sampling technique in this study was conducted by purposive sampling technique. Research instruments in data collection using tests, observation sheets, product assessment, questionnaires, and documentation. Data analysis techniques used the Normalized Gain test, Kruskal Walls Test and Simple Linear Regression test. The results showed an increase in understanding of the concept from the results of the pretest-posttest of students as much as 0.38 belonging to the medium category. The creativity profile of students resulted in the creativity of students in the category of quite creative. The magnitude of the influence between understanding the concept and creativity is indicated by the coefficient of determination of 0.320 which implies that the influence of the creativity variable on understanding the concept is 32%. One of the benefits of project-based learning can be used as an alternative model for learning the 2013 curriculum and zigzag books can be used as projects resulting from the implementation of project-based learning. In conclusion, this project-based learning can improve students' conceptual understanding and creativity by making zigzag books.